Challenges In Using WhatsApp as An Online Arabic Learning Center - A Syahid Robbani; Zulfa Amalia Wahidah; Ahmad Muzayyan Haqqy (Dinamika Ilmu, 2021)
This study aims to examine the challenges and obstacles faced in using WhatsApp as an online Arabic learning center and efforts to overcome them. The data from this qualitative study were obtained from observations of 71 students and 2 Arabic language teachers. The data was then validated and strengthened by interviews with 5 students and 2 Arabic language teachers. The results of this study show that the challenges and obstacles in using WhatsApp as an online Arabic learning center do not only come from students, student guardians, and teachers but can also come from the limitations of the WhatsApp application itself such as the maximum file size limit that can be sent and the record button prone to be canceled. In overcoming the existing obstacles, the teacher converts the files to be sent first, lowers the level of questions in assignments, pays attention to the accuracy of students' answers in doing assignments, and collaborates the use of WhatsApp with Google Drive and Instagram. Finally, by looking at the role of the WhatsApp application in the current learning process, the researcher hopes that the WhatsApp application developer will consider to provide WhatsApp for Education like WhatsApp for Business which has existed for a long time.